THE GENDER CONSTRUCTION IN DIALOGS PRESENTED IN â€œINTERLANGUAGEâ€ ENGLISH TEXTBOOK - Dewi, Salwa Atika (Pusat Pengembangan Bahasa IAIN Tulungagung, 2015)
One of the social aspects is gender. Gender is description of roles and responsibility between male and female in social context. Gender is important issues to be discussed because of always become controversial issues. The researcher tries to find out the impact of language to the society. Hopefully, the readers of textbook would be aware of stereotyping gender, which constructed in what they read. Of course, it is can be construct their mental and knowledge. As we know, textbook is not only as media to help teaching and learning process. It is also can be one of the products which have intention to sell. The central framework in this study was transitivity which the part of Systemic Functional Grammar. The data of this study are texts or written dialogues which consist of male and female characters. The source of data is e-book of ?Interlanguage? English textbook for student in eleventh grade of senior high school. The gender construction of the textbook is: female is dependent, emotional, and nice. Male is decision maker and rational.